Turbulence in rotating Bose-Einstein condensates - Amette Estrada, Julian (2022)
Since the idea of quantum turbulence was first proposed by Feynman and later realized in experiments of superfluid helium and Bose-Einstein condensates, much emphasis has been put on finding signatures that distinguish quantum turbulence from its classical counterpart. Here we show that quantum turbulence in rotating condensates is fundamentally different from the classical case. While rotating quantum turbulence develops a negative temperature state with self-organization of the kinetic energy in quantized vortices, it also displays an anisotropic dissipation mechanism and a different, non-Kolmogorovian, scaling of the energy at small scales. This scaling is compatible with Vinen turbulence and also has been found in recent simulations of condensates with multicharged vortices. An elementary explanation for the scaling is presented in terms of disorder in the vortices positions.